Nanometer composite nitrocellulose containing stabilizing agent and preparation method thereof

Nanocomplex nitrocellulose is prepared by electrospinning method, combining aniline, phenolurea and weak alkali salts and other nitrocellulose, which solves the problems of flammable and explosive nitrocellulose and uneven distribution of nitrocellulose, significantly improving its thermal stability and combustion performance.

CN119194640APending Publication Date: 2024-12-27NANJING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411412747.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Nitrocyte cellulose is flammable and explosive in application, and its thermal self-ignition leads to safety hazards in production, transportation, storage and use. Traditional mechanical mixing methods lead to uneven distribution of the stabilizer, affecting its stability.

Method used

Nanocomposite nitrocellulose is prepared by electrospinning. By uniformly mixing three types of tranquilizing agents such as aniline, phenolurea and weak alkali salts with nitrocellulose, nano-scale composite materials are formed. The electrospinning process parameters are optimized to prepare the diameter. Nanocomposite nitrocellulose below 80nm.

Benefits of technology

It effectively inhibits the thermal spontaneous combustion of nitrocellulose, extends its storage life, improves combustion performance and energy conversion efficiency, improves the performance of ignition explosives, and solves the problem of uneven distribution of the stabilizer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194640A_ABST
    Figure CN119194640A_ABST
Patent Text Reader

Abstract

The invention provides a stabilizing agent-containing nano composite nitrocellulose and a preparation method thereof, the stabilizing agent-containing nano composite nitrocellulose comprises a composite stabilizing agent and nitrocellulose in a mass ratio of 1: (19-35), and the composite stabilizing agent comprises aniline, phenylurea and a weak base salt. The nano-composite nitrocellulose containing the stabilizing agent is beneficial to improving the thermal stability of the nitrocellulose.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of energetic material preparation, and in particular relates to a nano composite nitrocellulose containing a stabilizer and a preparation method thereof. Background Art

[0002] Nitrocellulose (NC) is prepared by nitration of cellulose. It is widely used in the military field because of its high formation enthalpy. It is mainly used as propellant, propellant and explosive. The application field of nitrocellulose will be different according to the nitrogen content. Nitrocellulose with a nitrogen content of 11% to 13.5% is widely used as an energetic binder in single-base, double-base and triple-base propellants, modified double-base, composite modified double-base propellants and explosives. It is one of the important raw materials for explosives. However, in the application of nitrocellulose, its unfavorable characteristics such as flammability, explosiveness and instability are gradually exposed. These unfavorable characteristics are reflected in every link of its production, transportation, storage and use. Once used or stored improperly, nitrocellulose will directly undergo thermal decomposition or even thermal spontaneous combustion. Compared with the serious economic damage caused by thermal spontaneous combustion of nitrocellulose in the civilian field, thermal spontaneous combustion accidents caused by nitrocellulose in the military field often cause more serious accidents and have a great impact on the national defense military industry.

[0003] Studies on the mechanism of thermal spontaneous combustion of nitrocellulose show that nitrate groups are susceptible to thermal decomposition to produce autocatalytic substances such as nitrogen oxides, and trigger a series of autocatalytic reactions, shortening the safe storage life of nitrate-based energetic materials, especially solid propellants. Therefore, adding stabilizers is the most common measure. Commonly used stabilizers include aniline (phenylurea, phenol) derivatives and weak base salts. Scholars have conducted research on the stabilization effect and stabilization mechanism of these typical stabilizers. Katoh et al. compared the stabilization effect of DPA and antioxidant N-methyl-N,N'-diphenylurea (AKII) on the thermal spontaneous combustion of nitrocellulose and found that both stabilizers can effectively inhibit the thermal spontaneous combustion of nitrocellulose and prolong the storage time of nitrocellulose. They also studied the effects of weak alkaline salts and inorganic additives on the thermal stability of nitrocellulose and found that weak alkaline salts such as Li2CO3, Na2CO3, CaCO3, Mg(OH)2, and Ca(OH)2 can significantly prolong the induction period of thermal spontaneous combustion of nitrocellulose. The alkaline environment of pH 10-13 produced by the hydrolysis of this type of weak alkaline salt can inhibit the occurrence of denitrification reactions, thereby reducing the generation of NO2. Cieslak et al. from the Warsaw University of Technology in Poland studied the effects of stabilizers such as C2, AKⅡ and triphenylamine TPA on the thermal stability of nitrocellulose and found that TPA can improve the thermal stability of nitrocellulose and prolong the induction period of the autocatalytic reaction compared with the other three stabilizers. In the above studies, the stabilizer and nitrocellulose were prepared by a simple mechanical mixing method. Traditional nitrocellulose has a diameter of 20-40μm. Simple mechanical mixing will cause the distribution of the stabilizer to be uneven and easy to agglomerate after drying. The use of electrospinning to prepare nanocomposite nitrocellulose can make the sample mixed evenly and make the nitrocellulose and stabilizers of different components in good contact.

[0004] Electrospinning refers to the formation of nanofibers by establishing an electric field between a nozzle and a receiver. Under the action of the electric field force, the droplets on the nozzle detach under the influence of the high electric field force, the solution evaporates, condenses, and finally settles on the receiving device, thus forming nano nitrocellulose. In addition to ensuring that the nitrocellulose and the stabilizer are mixed evenly, the nano nitrocellulose prepared by this method has the characteristics of small size, high specific surface area, good mechanical stability, and large elastic modulus. At the same time, nano-spinning can improve the combustion performance of NC, improve the energy conversion efficiency, and thus improve the performance of NC-based explosives. Summary of the invention

[0005] In view of this, the present invention aims to overcome the defects in the prior art and proposes a nano-composite nitrocellulose containing a stabilizer and a preparation method thereof.

[0006] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0007] In a first aspect, the present invention provides a nano-composite nitrocellulose containing a stabilizer, comprising a composite stabilizer and nitrocellulose in a mass ratio of 1:(19-35), wherein the composite stabilizer comprises aniline, phenylurea and a weak base salt.

[0008] Preferably, the mass ratio of aniline, phenylurea and weak base salt in the composite stabilizer is (1-2): (1-5): (1-8).

[0009] Preferably, the aniline is selected from triphenylamine (TPA) and / or N-methyl-p-nitroaniline (MNA).

[0010] Preferably, the phenylurea is selected from 3-methyl-1,1-diphenylurea (AKII) and / or 1,3-dimethyl-1,3-diphenylurea (C2).

[0011] Preferably, the weak base salt is selected from lithium carbonate (Li2CO3) and / or sodium carbonate (Na2CO3).

[0012] In a second aspect, the present invention also provides a method for preparing the above-mentioned nanocomposite nitrocellulose containing a stabilizer, comprising the following steps:

[0013] The composite stabilizer and nitrocellulose are dissolved in a solvent to prepare an electrospinning precursor solution, the electrospinning precursor solution is electrospun through an electrospinning device, and nano-composite nitrocellulose is obtained after collection and drying.

[0014] Preferably, the solvent is acetone and NN dimethylformamide.

[0015] More preferably, the mass ratio of acetone to N-N-dimethylformamide in the solvent is 1:1.

[0016] Preferably, the mass fraction of nitrocellulose in the electrospinning precursor solution is 6 wt % to 14 wt %.

[0017] Preferably, the spinning voltage of the electrospinning device is 15-25 kV, and the propulsion rate is 0.5-1.0 mL h -1 , the receiving distance is 8 to 15 cm, the spinning temperature is 10 to 25°C, and the humidity is 30% to 60%.

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] (1) The present invention determines the electrospinning process parameters of stabilizer-containing nano nitrocellulose, which can efficiently prepare stabilizer-containing nano nitrocellulose with an average diameter of less than 80 nm.

[0020] (2) The present invention uses three types of stabilizers, namely aniline, phenylurea and weakly alkaline inorganic salts, to mix with nitrocellulose to prepare nano-composite nitrocellulose, thus filling the blank of the typical stabilizer adding method in nano-nitrocellulose.

[0021] (3) The three types of stabilizers used in the present invention can play a synergistic role. The addition of weak base salts can effectively inhibit the saponification reaction of stabilizers such as aniline and phenylurea, thereby enabling aniline and phenylurea stabilizers to better capture nitrogen oxides produced by thermal decomposition of nitrocellulose and alleviate the autocatalytic decomposition reaction of nitrocellulose. Phenylurea stabilizers mainly rely on capturing ROO free radicals to inhibit O2 from participating in the main reaction. In turn, nitrogen oxides are inhibited from reacting with the condensed phase that has not been broken, which can enable aniline stabilizers to react more fully with NO2 produced by the decomposition of nitrocellulose, effectively preventing the further occurrence of the autocatalytic reaction of nitrocellulose, thereby reducing the heat of reaction, which is conducive to maintaining the good thermal stability of phenylurea stabilizers.

[0022] (4) The present invention is the first to prepare nanocomposite nitrocellulose with a multi-component stabilizer uniformly dispersed by a co-spinning method, which can effectively improve the problem of uneven dispersion of the stabilizer.

[0023] (5) The stabilizer / nitrocellulose prepared by the present invention has a uniform and controllable diameter, which is suitable for the design of micro devices and can be used in the fields of micro propellants and micro detonators. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a diagram of the electrospinning device;

[0025] Figure 2 This is a SEM image of the nanocomposite nitrocellulose containing AKII / TPA / Li2CO3 (1:1:1) prepared in Example 1 of the present invention;

[0026] Figure 3 This is a SEM image of the nanocomposite nitrocellulose containing AKII / MNA / Li2CO3 (2:5:8) prepared in Example 2 of the present invention;

[0027] Figure 4 This is a SEM image of the nanocomposite nitrocellulose containing C2 / MNA / Na2CO3 (1:3:5) prepared in Example 3 of the present invention;

[0028] Figure 5 This is the SEM image of nitrocellulose prepared by conventional mechanical mixing method;

[0029] Figure 6 TG-DTG graph of the nanocomposite nitrocellulose containing AKII / TPA / Li2CO3 (1:1:1) prepared in Example 1 of the present invention and the nanocomposite nitrocellulose with a single component added;

[0030] Figure 7 The DSC graphs of the nanocomposite nitrocellulose containing AKII / TPA / Li2CO3 (1:1:1) and the nanocomposite nitrocellulose with a single component added prepared in Example 1 of the present invention;

[0031] Figure 8 TG-DTG graph of the nanocomposite nitrocellulose containing AKII / MNA / Li2CO3 (2:5:8) prepared in Example 2 of the present invention and the nanocomposite nitrocellulose with added single component;

[0032] Fig. 9 This is the DSC graph of the nanocomposite nitrocellulose containing AKII / MNA / Li2CO3 (2:5:8) prepared in Example 2 of the present invention and the nanocomposite nitrocellulose with a single component added.

[0033] Description of the drawings: 1. Syringe, 2. Micro-propulsion pump, 3. High voltage power supply, 4. Receiving device. DETAILED DESCRIPTION

[0034] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0035] The present invention is described in detail below in conjunction with embodiments.

[0036] Example 1

[0037] Under the environmental conditions of temperature of 25°C and relative humidity of 30%, 0.15g of composite stabilizer AKII / TPA / Li2CO3 (mass ratio of 1:1:1) was dissolved in a mixed solvent of acetone / N,N-dimethylformamide (mass ratio of 1:1), and after being fully dispersed and mixed in an ultrasonic stirrer, 2.85g of nitrocellulose was added, fully dissolved, and mixed evenly. A spinning precursor solution containing 14wt% nitrocellulose was prepared.

[0038] like Figure 1 As shown, the prepared spinning precursor solution is extracted with a syringe 1. After the extraction is completed, the syringe is placed on a micro-propellant pump 2. The diameter of the needle at the front end of the syringe is 0.6 mm. The needle is connected to a high-voltage power supply 3. The injection speed of the micro-propellant pump is set to 0.5 ml h -1 The distance between the needle and the receiving device 4 was adjusted to 10 cm, the high voltage power supply 3 was turned on, and the voltage was slowly adjusted to set it to 18 kV.

[0039] Example 2

[0040] Under the environmental conditions of temperature of 10°C and relative humidity of 53%, 0.095g of composite stabilizer AKII / MNA / Li2CO3 (mAKII:mMNA:mLi2CO3 is 2:5:8) is dissolved in a mixed solvent of acetone / N,N-dimethylformamide (mass ratio is 1:1), and then 3.325g of nitrocellulose is added after being fully dispersed and mixed in an ultrasonic stirrer, and fully dissolved and mixed. The spinning precursor solution containing nitrocellulose mass concentration of 9wt% is prepared.

[0041] like Figure 1 As shown, the prepared spinning precursor solution is extracted with a syringe 1. After the extraction is completed, the syringe is placed on a micro-propellant pump 2. The diameter of the needle at the front end of the syringe is 0.6 mm. The needle is connected to a high-voltage power supply 3. The injection speed of the micro-propellant pump is set to 0.5 ml h -1 The distance between the needle and the receiving device 4 was adjusted to 15 cm, the high voltage power supply 3 was turned on, and the voltage was slowly adjusted to set it to 20 kV.

[0042] Example 3

[0043] Under the environmental conditions of 10°C and 25% relative humidity, 0.1g of composite stabilizer C2 / MNA / Na2CO3 (mC2:mMNA:mNa2CO3 is 1:3:5) was dissolved in a mixed solvent of acetone / N,N-dimethylformamide, and then 2.0g of nitrocellulose was added after being fully dispersed and mixed in an ultrasonic stirrer, and fully dissolved and mixed. The spinning precursor solution containing nitrocellulose mass concentration of 6wt% was prepared.

[0044] like Figure 1 As shown, the spinning precursor solutions prepared in Examples 1 to 3 are extracted with a syringe 1. After the extraction is completed, the syringe is placed on a micro-propellant pump 2. The diameter of the needle at the front end of the syringe is 0.6 mm. The needle is connected to a high-voltage power supply 3. The injection speed of the micro-propellant pump is set to 0.6 mL h -1 The distance between the needle and the receiving device 4 was adjusted to 15 cm, the high voltage power supply 3 was turned on, and the voltage was slowly adjusted to set it to 20 kV.

[0045] In the electrospinning process, it can be observed that liquid is squeezed out from the front end of the needle. Under the action of the electrostatic field force, the liquid at the front end of the needle forms a regular and stable Taylor cone. When the electric field strength increases to a critical value, the electric field force will overcome the surface tension of the liquid to form a jet. It also produces an extremely high-frequency irregular spiral motion, the jet is rapidly stretched, and the solvent also evaporates rapidly, eventually forming a fiber with a diameter of nanometers.

[0046] Comparative Example 1

[0047] The preparation method of the nano-composite nitrocellulose in this comparative example is different from that in Example 1 in that the stabilizer used is a single stabilizer AKII.

[0048] Comparative Example 2

[0049] The preparation method of the nano-composite nitrocellulose in this comparative example is different from that in Example 1 in that the stabilizer used is a single stabilizer TPA.

[0050] Comparative Example 3

[0051] The preparation method of the nano-composite nitrocellulose in this comparative example is different from that in Example 1 in that the stabilizer used is a single stabilizer Li2CO3.

[0052] Comparative Example 4

[0053] The preparation method of the nano-composite nitrocellulose in this comparative example is different from that in Example 1 in that the composite stabilizer selected as the stabilizer is AKII / Li2CO3.

[0054] Comparative Example 5

[0055] The preparation method of the nano-composite nitrocellulose in this comparative example is different from that in Example 1 in that the composite stabilizer selected as the stabilizer is TPA / Li2CO3.

[0056] Comparative Example 6

[0057] The preparation method of the nano-composite nitrocellulose in this comparative example is different from that in Example 1 in that the composite stabilizer selected as the stabilizer is AKII / TPA.

[0058] Comparative Example 7

[0059] The preparation method of the nanocomposite nitrocellulose in this comparative example is different from that in Example 1 in that the mass ratio of AKII / TPA / Li2CO3 is 1:1:9.

[0060] Comparative Example 8

[0061] The preparation method of the nanocomposite nitrocellulose in this comparative example is different from that in Example 1 in that the mass ratio of AKII / TPA / Li2CO3 is 1:6:8.

[0062] Comparative Example 9

[0063] The preparation method of the nano-composite nitrocellulose in this comparative example is different from that in Example 1 in that the nano-nitrocellulose is prepared by a conventional mechanical mixing method.

[0064] like Figure 2-4 Shown are SEM images of composite nitrocellulose containing various stabilizers prepared in Examples 1 to 3. Figure 5This is a SEM image of conventional composite nitrocellulose. Figure 6-Figure 9 It can be seen that the autocatalytic reaction rate, heat release and heat flow value of nitrocellulose with three stabilizers added at the same time are all lower than those of the sample with only one stabilizer added. Figure 5 It can be seen that the electrospinning method effectively reduces the diameter of NC and nanosizes conventional NC. The nano nitrocellulose prepared in Examples 1 to 3 and Comparative Examples 1 to 9 was tested for autocatalytic reaction rate, heat release and heat flow value, and the test results are as follows:

[0065] Table 1 Test results

[0066]

[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A nanocomposite nitrocellulose containing a stabilizer, characterized in that: The invention comprises a composite stabilizer and nitrocellulose in a mass ratio of 1:(19-35), wherein the composite stabilizer comprises aniline, phenylurea and weak base salt.

2. The nanocomposite nitrocellulose according to claim 1, characterized in that: The mass ratio of aniline, phenylurea and weak base salt in the composite stabilizer is (1-2): (1-5): (1-8).

3. The nanocomposite nitrocellulose according to claim 1, characterized in that: The aniline is selected from triphenylamine and / or N-methyl-p-nitroaniline.

4. The nanocomposite nitrocellulose according to claim 1, characterized in that: The phenylurea is selected from 3-methyl-1,1-diphenylurea and / or 1,3-dimethyl-1,3-diphenylurea.

5. The nanocomposite nitrocellulose according to claim 1, characterized in that: The weak base salt is selected from lithium carbonate and / or sodium carbonate.

6. The method for preparing the nanocomposite nitrocellulose containing a stabilizer according to any one of claims 1 to 5, characterized in that: The steps include: The composite stabilizer and nitrocellulose are dissolved in a solvent to prepare an electrospinning precursor solution, the electrospinning precursor solution is electrospun through an electrospinning device, and nano-composite nitrocellulose is obtained after collection and drying.

7. The method for preparing the nanocomposite nitrocellulose containing a stabilizer according to claim 6, characterized in that: The solvents are acetone and NN dimethylformamide.

8. The method for preparing nanocomposite nitrocellulose containing a stabilizer according to claim 7, characterized in that: The mass ratio of acetone to N-N-dimethylformamide in the solvent is 1:

1.

9. The method for preparing nanocomposite nitrocellulose containing a stabilizer according to claim 6, characterized in that: The mass fraction of nitrocellulose in the electrospinning precursor solution is 6 wt % to 14 wt %.

10. The method for preparing nanocomposite nitrocellulose containing a stabilizer according to claim 6, characterized in that: The spinning voltage of the electrospinning device is 15-25 kV, and the propulsion rate is 0.5-1.0 mL h -1 , the receiving distance is 8 to 15 cm, the spinning temperature is 10 to 25°C, and the humidity is 30% to 60%.